X-Linked Lissencephaly with Absent Corpus Callosum - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Three new cases of the congenital syndrome consisting of X-linked lissencephaly, absent corpus callosum, and genital anomalies (XLAG) are reported from the University Hospital, Angers, France.